ANALISIS DIKSI DAN GAYA BAHASA PADA IKLAN LAYANAN MASYARAKAT DI INSTAGRAM SATGAS PERUBAHAN PERILAKU SERTA PEMANFAATANNYA SEBAGAI BAHAN AJAR TEKS IKLAN DI SMP - Aulia, Risa; Triyadi, Slamet; Pratiwi, Wienike Dinar (Diglosia : Jurnal Pendidikan, Kebahasaan, dan Kesusastraan Indonesia, 2023)
AbstrackÂ Each individual has its own characteristics to express the language that is in their thoughts and feelings. Through self-expression, a diction (word choice) and language style is created. In an advertisement, diction and language style are needed in order to attract the interest of the audience. Especially in public service advertisements. One of them is on the Task Force for Change Instagram account which contains lots of pictures related to information and prevention of the corona virus (covid-19) which is intended for all people to stay alert and carry out health programs properly. The purpose of this study was to describe diction and language style, as well as the use of teaching materials. This study uses a descriptive approach. The analysis was carried out by documentation, listening and recording, then analyzed using Gorys Keraf's theory. The research findings show that there is diction, denotative meaning, connotative meaning, common words, special words, abstract words, concrete words, popular words, and foreign words. Language style, namely, formal language style, informal language style, conversational style, simple style, noble and powerful style, medium style, climax, parallelism, and repetition. Thus, it can be used as teaching material on advertising text materials, slogans, and posters at the odd semester grade VIII Junior High School level, namely in the form of handouts.Â Keywords: Diction, Language Style, Public Service Advertisement, Ad Text.Â